Pterostilbene Is a Potential Candidate for Control of Blackleg in Canola. - Joshua C O Koh; Denise M Barbulescu; Phil A Salisbury; Anthony T Slater (PLoS ONE, 2016)
Two stilbenes, resveratrol and pterostilbene, exhibit antifungal activity against Leptosphaeria maculans, the fungal pathogen responsible for blackleg (stem canker) in canola (Brassica napus). In vitro studies on the effect of these stilbenes on L. maculans mycelial growth and conidia germination showed that pterostilbene is a potent fungicide and sporicide, but resveratrol only exerted minor inhibition on L. maculans. Cell viability of hyphae cultures was markedly reduced by pterostilbene and SYTOX green staining showed that cell membrane integrity was compromised. We demonstrate that pterostilbene exerts fungicidal activity across 10 different L. maculans isolates and the compound confers protection to the blackleg-susceptible canola cv. Westar seedlings. The potential of pterostilbene as a control agent against blackleg in canola is discussed.